2016
DOI: 10.1016/j.renene.2015.07.086
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating-water-column wave energy converters and air turbines: A review

Abstract: a b s t r a c tThe ocean waves are an important renewable energy resource that, if extensively exploited, may contribute significantly to the electrical energy supply of countries with coasts facing the sea. A wide variety of technologies has been proposed, studied, and in some cases tested at full size in real ocean conditions. Oscillating-water-column (OWC) devices, of fixed structure or floating, are an important class of wave energy devices. A large part of wave energy converter prototypes deployed so far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
320
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 703 publications
(382 citation statements)
references
References 91 publications
0
320
0
3
Order By: Relevance
“…The extracted energy is generally converted into electrical energy, and these innovative devices are commonly denominated Wave Energy Converters (hereafter WECs). Although more than 1000 WECs have been patented worldwide (Falcão and Henriques, 2016), this technology is currently in an early stage of development. A serious break on the growth and commercialization of these devices are their costs, still very high when compared with other more established renewable energy technologies such as wind turbines or solar panels, and their potential environmental risks (Azzellino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracted energy is generally converted into electrical energy, and these innovative devices are commonly denominated Wave Energy Converters (hereafter WECs). Although more than 1000 WECs have been patented worldwide (Falcão and Henriques, 2016), this technology is currently in an early stage of development. A serious break on the growth and commercialization of these devices are their costs, still very high when compared with other more established renewable energy technologies such as wind turbines or solar panels, and their potential environmental risks (Azzellino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A serious break on the growth and commercialization of these devices are their costs, still very high when compared with other more established renewable energy technologies such as wind turbines or solar panels, and their potential environmental risks (Azzellino et al, 2013). Other important constraints are the operational efficiency and the structural survivability of the devices, nowadays still low considering that several devices have been partially or, even more, completely destroyed during extreme storms (Medina-Lopez et al, 2015;Falcão and Henriques, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently the successful deployment of a OWC at Jeju Island, South Korea, worked at rated power of 500 kW. These successful devices show that the obstacles can be overcome with further research [6]. Table 1 summarizes most of the OWC devices that have been installed in various countries with the real or expected capacity and the turbine type that was used to extract the power.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed model has experienced various stages of development and research. Dorrell [6] describes the construction of a small multi-chambered OWC system. Then Hsieh et al [7] developed and analysed a two chamber OWC; they validated the increase in power output due to the use of the multiple chamber arrangement experimentally based on the wave conditions around Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…12 A recent review on the development of the OWC devices and air turbines has been given by Falcao and Henriques. 17 To understand and improve their power performance by the OWC devices, numerical methods have been developed and employed. Earlier theoretical work on the hydrodynamic performance of some simple OWCs has shown that the OWC devices could have a high primary wave energy conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%